2015
DOI: 10.1007/s00709-015-0905-3
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Agrobacterium tumefaciens-mediated genetic transformation of graminaceous crops

Abstract: Steady increase in global population poses several challenges to plant science research, including demand for increased crop productivity, grain yield, nutritional quality and improved tolerance to different environmental factors. Transgene-based approaches are promising to address these challenges by transferring potential candidate genes to host organisms through different strategies. Agrobacterium-mediated gene transfer is one such strategy which is well known for enabling efficient gene transfer in both mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 169 publications
0
38
0
Order By: Relevance
“…To obtain this plasmid, a Ssp I/ Bam HI fragment from pBSK-ALS containing the entire ALS coding region was fused to the maize ubiquitin ( ubi ) promoter (Christensen and Quail, 1996), inserted into the cloning vector pBSK- and then transferred into pH001-VS, a pS001 derivative (Reiss et al, 1996) in which the RK2 origin of replication was replaced with the one of pVS1 and the Sulfonamide resistance gene exchanged for the intron-split hygromycin resistance gene of pWBVec8 (Wang et al, 1998). The S629N mutation was introduced into the ALS gene by oligo-directed mutagenesis using PCR and oligos S629N PmlI FWD (GAG CAC GTG CTG CCT ATG ATC CCA AAC GGT GCT TTC AAG GAC) and S629NSbfIREV (GGC ATG CAC ATA CAA ATG GAC) and replacement of the wild type with the mutant sequences on the Pml I/ Sbf I fragment.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain this plasmid, a Ssp I/ Bam HI fragment from pBSK-ALS containing the entire ALS coding region was fused to the maize ubiquitin ( ubi ) promoter (Christensen and Quail, 1996), inserted into the cloning vector pBSK- and then transferred into pH001-VS, a pS001 derivative (Reiss et al, 1996) in which the RK2 origin of replication was replaced with the one of pVS1 and the Sulfonamide resistance gene exchanged for the intron-split hygromycin resistance gene of pWBVec8 (Wang et al, 1998). The S629N mutation was introduced into the ALS gene by oligo-directed mutagenesis using PCR and oligos S629N PmlI FWD (GAG CAC GTG CTG CCT ATG ATC CCA AAC GGT GCT TTC AAG GAC) and S629NSbfIREV (GGC ATG CAC ATA CAA ATG GAC) and replacement of the wild type with the mutant sequences on the Pml I/ Sbf I fragment.…”
Section: Methodsmentioning
confidence: 99%
“…Genus Agrobacterium includes several species of bacteria commonly found in soil capable of forming tumors on the stems and roots of plants and trees (Singh and Prasad, 2016). Consistent with this phenotype, introduction of Agrobacterium T-DNA into the plant genome results in tumor formation (Bourras et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its efficiency, this system had many advancements, including developed in vitro plant propagation system, incubation and selection methods, and use of hyper-virulent strains of Agrobacterium tumefaciens [32]. The transformation efficiency has also been enhanced during this investigation by adding acetosyringone to induce the activity of vir genes.…”
Section: Culture Selection and Explant Regeneration Of Putative Transmentioning
confidence: 99%
“…Furthermore, El-Rakashy et al [37] showed that the transgenic date palm expressing endotoxin Cry3Aa gene was in field evaluated for red palm weevil resistance, yield and fruit quality. The higher transformation efficiency has been achieving by the use of super-binary vectors with the hyper-virulent strain [32]. Choice of a powerful promoter that is constitutively expressed is important to ensure success and good constitutive expression of the foreign gene in a new environment, i.e., in a transgenic plant.…”
Section: Transgenic Date Palm Containing Endotoxin Cry3aamentioning
confidence: 99%